Reduced USP22 Expression Impairs Mitotic Removal of H2B Monoubiquitination, Alters Chromatin Compaction and Induces Chromosome Instability That May Promote Oncogenesis - Jeusset, Lucile M. (Cancers (Basel), 2021)
SIMPLE SUMMARY: Chromosome instability (CIN) promotes cancer initiation and progression, but its genetic origins remain largely unknown. As aberrant mitotic processes such as chromatin compaction defects can induce CIN, characterizing the molecular determinants of mitotic fidelity may reveal novel CIN genes. In vitro, monoubiquitination of histone H2B at lysine 120 (H2Bub1) impairs chromatin compaction, while in vivo H2Bub1 is rapidly depleted in early mitosis. USP22 is a major deubiquitinating enzyme catalyzing H2Bub1 removal in interphase and may also be responsible for H2Bub1 depletion in mitosis. To assess whether mitotic removal of H2Bub1 is required for mitotic fidelity, we employ complementary genetic and single-cell imaging microscopy approaches to assess the impact reduced USP22 expression has on H2Bub1 abundance, chromatin compaction and chromosome stability. We show that USP22 deficiency impairs H2Bub1 removal and induces chromatin compaction defects. Further, we identify USP22 as a novel CIN gene, indicating that USP22 deletions in tumors may drive CIN and contribute to oncogenesis. ABSTRACT: Chromosome instability (CIN) is an enabling feature of oncogenesis associated with poor patient outcomes, whose genetic determinants remain largely unknown. As mitotic chromatin compaction defects can compromise the accuracy of chromosome segregation into daughter cells and drive CIN, characterizing the molecular mechanisms ensuring accurate chromatin compaction may identify novel CIN genes. In vitro, histone H2B monoubiquitination at lysine 120 (H2Bub1) impairs chromatin compaction, while in vivo H2Bub1 is rapidly depleted from chromatin upon entry into mitosis, suggesting that H2Bub1 removal may be a pre-requisite for mitotic fidelity. The deubiquitinating enzyme USP22 catalyzes H2Bub1 removal in interphase and may also be required for H2Bub1 removal in early mitosis to maintain chromosome stability. In this study, we demonstrate that siRNA-mediated USP22 depletion increases H2Bub1 levels in early mitosis and induces CIN phenotypes associated with mitotic chromatin compaction defects revealed by super-resolution microscopy. Moreover, USP22-knockout models exhibit continuously changing chromosome complements over time. These data identify mitotic removal of H2Bub1 as a critical determinant of chromatin compaction and faithful chromosome segregation. We further demonstrate that USP22 is a CIN gene, indicating that USP22 deletions, which are frequent in many tumor types, may drive genetic heterogeneity and contribute to cancer pathogenesis.